1990
DOI: 10.7567/jjaps.29s1.137
|View full text |Cite
|
Sign up to set email alerts
|

Study on SAW Streaming and its Application to Fluid Devices

Abstract: Various liquid motions such as streaming and droplet formation on the surface of SAW propagation substrate are called SAW streaming. Experiments on SAW streaming using 128° rot. Y–X LiNbO3 at the frequency of 50 MHz with various pulse widths are described. Surface treatment of SAW substrate by silanization is employed to demonstrate the droplet ejection. Theoretically, SAW streaming force can be derived using the acoustic streaming theory. The calculated SAW streaming force is found to be ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 0 publications
0
56
0
Order By: Relevance
“…An upper bound for the effective body force invoked by gradients in the sound field along the SAW propagation axis in the fluid [12] can be determined from an upper bound for the rate of sound attenuation along the film. We estimate this upper bound for the sound attenuation rate by neglecting reflections of sound off the free surface of the film, so that the sound field in (4.2) is attenuated strictly owing to the SAW attenuation, a common approach [13], because its attenuation length (measured in millimetres for most fluids) is three orders of magnitude smaller than the attenuation length of sound in the film (in the range of metres) [14].…”
Section: Critical Transition Thickness H C 2 Between Thick and Intermmentioning
confidence: 99%
“…An upper bound for the effective body force invoked by gradients in the sound field along the SAW propagation axis in the fluid [12] can be determined from an upper bound for the rate of sound attenuation along the film. We estimate this upper bound for the sound attenuation rate by neglecting reflections of sound off the free surface of the film, so that the sound field in (4.2) is attenuated strictly owing to the SAW attenuation, a common approach [13], because its attenuation length (measured in millimetres for most fluids) is three orders of magnitude smaller than the attenuation length of sound in the film (in the range of metres) [14].…”
Section: Critical Transition Thickness H C 2 Between Thick and Intermmentioning
confidence: 99%
“…The window for jetting is indeed narrow, between the effects of less power in simply moving the drop and the effects of more power that tend to atomize the drop. Shiokawa et al (1990) reported the phenomenon many years ago, and there it remained something of a curiosity until some additional work was done to understand the nature of the jet formation and to consider the behavior of the fluid from a microfluidics perspective, as taken by and shown in Fig. 14.…”
Section: Jetting and Levitationmentioning
confidence: 99%
“…More recently, acoustic streaming is the subject of a burst of interest with the development of microfluidic applications [7,8]. For instance, it is at the core of the physics involved in droplets actuation with Surface Acoustic Waves (SAW) [9] for lab-on-a-chip facilities, providing a versatile tool for droplet displacement [10][11][12], atomization [13], jetting [14,15] or vibration [12,16,17]. Moreover, vorticity associated with acoustic streaming is the main envisioned phenomenon to ensure efficient mixing of liquids [18,19].…”
Section: Introductionmentioning
confidence: 99%